2014
DOI: 10.5455/ovj.2014.v4.i1.p20
|View full text |Cite
|
Sign up to set email alerts
|

TRIXcell+, a new long-term boar semen extender containing whey protein with higher preservation capacity and litter size

Abstract: It was the aim of the present study to test whey as protective protein for the sperm cell in the long-term boar semen preservation medium TRIXcell. Analyses of sperm cell motility using computer-assisted semen analysis (CASA) indicated that the whey protein Porex has a similar protective effect as bovine serum albumin (BSA) in maintaining viability of stored boar sperm. Boar sperm diluted in TRIXcell+ maintains commercially acceptable motility (>60%) for 10 days, while swine sperm diluted in the semen prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…The mean percentage of sperm motility at each hour of preservation in Modena was significantly higher (P<0.05) than GEPS extender. Similar findings were also obtained by Bania (2017), van den Berg et al (2014) and Saikia et al (2016) who recorded significantly lower sperm motility in TRIXcell+, Modena and GEPS extenders. The significantly higher sperm motility in TRIXcell+ extender is unknown as its composition is a commercial secret.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The mean percentage of sperm motility at each hour of preservation in Modena was significantly higher (P<0.05) than GEPS extender. Similar findings were also obtained by Bania (2017), van den Berg et al (2014) and Saikia et al (2016) who recorded significantly lower sperm motility in TRIXcell+, Modena and GEPS extenders. The significantly higher sperm motility in TRIXcell+ extender is unknown as its composition is a commercial secret.…”
Section: Resultssupporting
confidence: 88%
“…The conception rate following AI with fresh diluted semen (N=25) and semen preserved for 24 (N=5), 48 (N=3), 72 (N=3), 96 (N=2) and 120 (N=2) h was 80, 80, 66.67, 66.67, 100 and 50%, respectively. van den Berg et al (2014) also reported better farrowing rate and litter size for semen diluted in TRIXcell+ and stored for 5 days on farm fertility performance. However, in the present study, the data were inconclusive of the fertility efficacy of TRIXcell+ extender as the insemination number was very less and not done on equal number of females and hence, the result was variable for different age of semen used.…”
Section: Resultsmentioning
confidence: 87%